2023
DOI: 10.3390/jof9010116
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Depsides and Tridepsides: Progress in Pharmacological Approaches

Abstract: Depsides and tridepsides are secondary metabolites found in lichens. In the last 10 years, there has been a growing interest in the pharmacological activity of these compounds. This review aims to discuss the research findings related to the biological effects and mechanisms of action of lichen depsides and tridepsides. The most studied compound is atranorin, followed by gyrophoric acid, diffractaic acid, and lecanoric acid. Antioxidant, cytotoxic, and antimicrobial activities are among the most investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…[30] As for plants, lichens are rich in several metabolites from which they produce more than 1000 compounds. [10,48] In Figure 6. Evolution of corrosion rates as a function of time with and without the inhibitor in an acidic medium HCl (1 M) addition, they are producers of original compounds and more specifically of bioactive secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] As for plants, lichens are rich in several metabolites from which they produce more than 1000 compounds. [10,48] In Figure 6. Evolution of corrosion rates as a function of time with and without the inhibitor in an acidic medium HCl (1 M) addition, they are producers of original compounds and more specifically of bioactive secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…As for plants, lichens are rich in several metabolites from which they produce more than 1000 compounds [10,48] . In addition, they are producers of original compounds and more specifically of bioactive secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of compounds reported in lichens and classified in the groups of dibenzofurans, depsides, depsidones, depsones, lactones, quinones, and pulvinic acid derivatives are highly complex due to their synthesis through various biosynthetic pathways and their potential medicinal use as antibiotics, antitumor/antimutagenic, antiviral, enzyme inhibitor, and antioxidants (Bostie and Grube, 2005;Ureña-Vacas et al, 2022a;Ureña-Vacas et al, 2023). The lichen genera that group most species with reported biological activities are Acarospora, Alectoria, Bryoria, Bulbothrix, Candelariella, Cetraria, Cetrelia, Cladia, Cladonia, Dirinaria, Evernia, Heterodermia, Hypogymnia, Lethariella, Lobaria, Melanelixia, Myelochroa, Parmelia, Parmotrema, Peltigera, Platismatia, Pleurosticta, Pseudevernia, Pseudoparmelia, Ramalina, Stereocaulon, Sticta, Teloschistes, Thamnolia, Umbilicaria, Usnea, Vulpicida, and Xanthoparmelia; on the other hand, the isolated compounds with more biological evidence are atranorin, barbatic, diffractaic, evernic, fumarprotocetraric, gyrophoric, lobaric, orsellinic, physodic, protocetraric, usnic, and vulpinic acids (Adenubi et al, 2022).…”
Section: Qualitative Analysis Of Phytoconstituents Of Lichen Extractsmentioning
confidence: 99%
“…[5,6] In literature, it was found that some of lichen also biosynthesized chloroatranorin along with atranorin, depsides and tridepsides. [47] It has also been credited as anti-bacterial, [48] and anti-biotic. [49][50][51] Some of secondary metabolites present in lichens act as very good preventive agent to protect neurological disorders [36][37][38][39][40] such as Alzheimer's disease by performing cholinesterase activity.…”
Section: Introductionmentioning
confidence: 99%